2018
DOI: 10.1177/0897190018760645
|View full text |Cite
|
Sign up to set email alerts
|

Mirtazapine-Induced Pancreatitis—A Case Report

Abstract: Acute pancreatitis has numerous etiologies, with the most common including gallstones, alcohol abuse, and medications such as angiotensin-converting enzyme (ACE) inhibitors, statins, and diuretics. Mirtazapine has been associated with increased serum cholesterol and serum triglyceride levels. However, few studies have reported dangerously elevated triglyceride levels resulting in acute pancreatitis. This report discusses a case of mirtazapine-induced pancreatitis in a 46-year-old African American female. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 6 publications
1
7
0
Order By: Relevance
“…The preliminary search retrieved a total of 158 studies, of which 8 met the inclusion criteria. [20][21][22][23][24][25][26][27] The quality assessment of these 8 studies with the adapted Newcastle-Ottawa Scale is shown in Table 1.…”
Section: Results Of the Literature Searchmentioning
confidence: 99%
See 1 more Smart Citation
“…The preliminary search retrieved a total of 158 studies, of which 8 met the inclusion criteria. [20][21][22][23][24][25][26][27] The quality assessment of these 8 studies with the adapted Newcastle-Ottawa Scale is shown in Table 1.…”
Section: Results Of the Literature Searchmentioning
confidence: 99%
“…These findings further strengthen the possibility that several possible mechanisms are involved in mirtazapine's adverse action on the pancreas. 21,24,26 Various mechanisms of adverse action are then reflected in the diversity of severity levels of the pancreatitis, resulting in the implementation of different treatment methods (in the cases described here, 1 patient required surgery while other patients were treated using a pharmacological approach). This diversity in severity and outcomes highlights the importance of considering mirtazapine involvement, especially in the etiology of severe forms of pancreatitis (with a harsh clinical picture and visible necrosis on imaging).…”
Section: Discussionmentioning
confidence: 99%
“…MIRT-induced pancreatitis has been reported in a 46-year-old African-American woman. The woman developed pancreatitis; therefore, MIRT was discontinued as the probable reason for her hypertriglyceridemia-induced pancreatitis ( Bowers et al, 2019 ). The side effects of MIRT, including psychomotor restlessness and akathisia, are described as warnings, which affect<1 % of the populace ( Koller, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Hypertriglyceridemia has also been described as occasionally occurring with antidepressant medications. Perhaps best described is the HTG in patients treated with the tetracyclic antidepressant mirtazapine, in which 6% of patients were reported to have triglyceride levels >500 mg/dl (101) and there are several reports of HTG-associated acute pancreatitis occurring in patients treated with mirtazapine (102).…”
Section: Antipsychotics and Antidepressantsmentioning
confidence: 99%